Cold plasma treatment of catalytic materials: a review. (1st June 2021) - Di, Lanbo; Zhang, Jingsen; Zhang, Xiuling; Wang, Hongyang; Li, Hong; Li, Yanqin; Bu, Decai
Abstract: Catalytic materials play important roles in chemical, energy, and environmental fields. The exhaustion of fossil fuels and the resulting deteriorative environment have become worldwide problems to be solved urgently. Therefore, treatment of catalytic materials by a green process is required for a sustainable future, and the atom efficiency of the catalytic materials should be improved at the same time. Cold plasma is rich in high-energy electrons and active species, and the gas temperature can be close to room temperature. It has been proved to be a fast, facile, and environmentally friendly novel method for treating catalytic materials, and has aroused increasing research interests. First, plasma treatment can achieve the reduction, deposition, combination, and decomposition of active components during the preparation of catalytic materials. The fast, low-temperature plasma process with a strong electric field in it leads to different types of nucleation and crystal growth compared to conventional thermal methods. Correspondingly, the synthesized catalytic materials generally possess smaller particle sizes and controlled structure depending on the plasma processing parameters and the materials to be treated, which can enhance their activity and stability. Second, plasma treatment can achieve the modification, doping, etching, and exfoliation of the catalytic materials, which can tune the surface properties and electronic structures of the catalytic materials to expose more active sites. Third, plasma treatment can regenerate deactivated catalytic materials by removing the carbon deposits or other poisons, and reconstruction of the destroyed structure. This work reviews the current status of research on cold plasma treatment of catalytic materials. The focus is on physical and chemical processes during plasma processing, the processing mechanism of the catalytic materials, as well as the future challenges in this filed.